2015
DOI: 10.3892/ol.2015.3993
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-362-5p inhibits proliferation, migration and invasion of human breast cancer MCF7 cells

Abstract: Abstract. An increasing number of studies have indicated that the deregulation of microRNAs (miRNAs) contributes to tumorigenesis and metastasis. In the present study, significant upregulation of miR-362-5p was identified in the breast cancer MDA-MB-231 and MCF7 cell lines compared with the control CCD-1095Sk cell line. The inhibition of miR-362-5p was demonstrated to significantly inhibit the cell proliferation, migration and invasion of human breast cancer MCF7 cells. In addition, the knockdown of miR-362-5p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…miR‐130b is overexpressed in metastatic renal cell carcinomas and is a member of a 4‐miRNA signature that is predictive of the risk of tumour metastasis . Inhibition of hsa‐miR‐362‐5p (cfa‐miR‐362 homologue) has been shown to decrease the proliferation, migration and invasion of MCF7 breast cancer cells, and the growth and metastasis of hepatocellular carcinoma cells in vivo . Conversely, down‐regulation of hsa‐miR‐124‐3p (homologue of cfa‐miR‐124) in numerous cancers and hsa‐miR‐548c‐3p (mml‐miR‐548c homologue) in breast cancer implies a metastasis suppressor role.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐130b is overexpressed in metastatic renal cell carcinomas and is a member of a 4‐miRNA signature that is predictive of the risk of tumour metastasis . Inhibition of hsa‐miR‐362‐5p (cfa‐miR‐362 homologue) has been shown to decrease the proliferation, migration and invasion of MCF7 breast cancer cells, and the growth and metastasis of hepatocellular carcinoma cells in vivo . Conversely, down‐regulation of hsa‐miR‐124‐3p (homologue of cfa‐miR‐124) in numerous cancers and hsa‐miR‐548c‐3p (mml‐miR‐548c homologue) in breast cancer implies a metastasis suppressor role.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, a number of miRNAs have been reported to affect growth and metastasis. For example, miR-362-5p may target CYLD lysine 63 deubiquitinase to inhibit the proliferation, migration and invasion of breast cancer cells (26). Zhang et al (27) reported that miR-147 repressed the growth and metastasis of breast cancer through the Akt/mechanistic target of rapamycin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐362‐5p inhibits (Ni et al, ; Zou et al, ) or promotes (Ni et al, ) a variety of cancers. Recently, its overexpression has been shown to contribute to HCC malignancy (Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%